Analysis of The Implementation on Community Empowerment Policies in Denpasar, Bali, Indonesia - Junaedy, I Kadek Dede; I Made Sumada; Azhari Aziz Samudra (Jurnal Studi Pemerintahan, 2024)
This research aimed at understanding the implementation concerning the Denpasar Municipality government policy which is called “Kube". Kube is a form of community joint business group program that aims to empower village communities in the form of cash assistance. This research used a qualitative approach and explores the opinions of key informants. The results of the analysis showed that various problems in the field caused the “Kube” program to be ineffective due to limited facilities and infrastructure, small development capital and the absence of final marketing of home industry products. Eventually, it became one of the causes of high poverty rates in villages. To overcome this problem, the government is expected to provide greater capital, create a marketing network for home industry products, and train community groups and provide technical assistants in the field